The Essence of Islam: Conceptual Analysis between Aqidah, Sharia, and Morals - Himmatul Khoiriyah; Madya Dr. Jasni bin Sulong (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
Islamic law represents a comprehensive legal system derived from divine revelation that governs various aspects of human life. Understanding its philosophical foundation is essential to distinguish between the immutable principles of Sharia and the dynamic interpretations developed through fiqh and ushul fiqh. This study aims to analyze the concepts of Sharia, fiqh, and Islamic law and to examine the philosophical relationship among these three fundamental elements within the framework of Islamic legal philosophy. The research employs a normative juridical method using conceptual and theological-normative approaches. Primary legal materials consist of the Qur'an and Hadith, while secondary and tertiary sources include classical and contemporary scholarly works, scientific journals, books, dictionaries, and encyclopedias. Data were collected through library research and analyzed using a descriptive-analytical method. The findings reveal that Sharia constitutes the divine and absolute legal foundation established by Allah, whereas fiqh represents the human understanding and interpretation of Sharia through the process of ijtihad. Ushul fiqh functions as the methodological framework that guides the derivation and formulation of Islamic legal rulings from their authoritative sources. The study further demonstrates that these three components are inseparable and collectively establish a coherent legal system that balances revelation with rational reasoning. A philosophical approach to Islamic law highlights not only its normative character but also its underlying objectives, including justice, public welfare (maslahah), and the realization of the maqasid al-shariah. Consequently, Islamic law should be understood as a dynamic legal system capable of responding to contemporary social developments while maintaining its essential religious values and universal principles.